Ketimpangan Hak Dan Kewajiban Pasangan Mahasiswa Prespektif Kompilasi Hukum Islam: Studi Kasus Pasangan Suami Istri Mahasiswa Universitas Nurul Jadid - Ainul Yakin; Syamsul Ma'arif (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study aims to analyze the inequality in the fulfillment of rights and responsibilities in married couples who are still students, and to understand this phenomenon based on the perspective of the Compilation of Islamic Law (KHI). The background of this study is the increasing number of marriages among students, which raises challenges in balancing academic and household roles. Using a qualitative method with a descriptive approach, data were collected through interviews and observations of student couples at Nurul Jadid University. The study results show inequality where the husband focuses more on financial responsibility, while the wife is dominant in managing the household. In general, fulfilling these rights and obligations is in line with the principles in the KHI, but is not optimal, especially in the division of domestic tasks. Factors causing inequality include academic pressure, lack of social support, and cultural expectations of the roles of husband and wife. This study emphasizes the importance of building equality of rights and responsibilities to achieve household harmony. These findings provide insight into the dynamics of student couples within the framework of Islamic law and offer recommendations so that married students can carry out academic and household roles in a balanced manner.